Autophagic dysregulation triggers innate immune activation in glucocerebrosidase deficiency - Magda L. Atilano; Alexander J. Hull; Kerri J. Kinghorn (Autophagy Reports)
Mutations in the GBA1 (glucosylceramidase beta 1) gene cause the most common lysosomal storage disorder, Gaucher disease (GD), characterized by the lysosomal accumulation of glucosylceramide and lysosomal dysfunction. Downstream of defects in lysosomal-autophagosome fusion, GD cells display autophagic dysfunction. Immune activation and inflammation are also known features of GD pathogenesis. However, the precise link between autophagy and immune activation, and the tissue-specific nature of these pathologies, are yet to be determined. Here we summarize our recent manuscript, which probes the role of autophagy in stimulating a chronic innate immune response in a Drosophila GD model. The gut-brain axis is increasingly being implicated in disease pathology, and accordingly, we demonstrated gastrointestinal dysfunction and gut microbiome dysbiosis in GD flies. Moreover, intestinal cells display lysosomal-autophagic defects like those seen in the GD fly brain. Stimulation of autophagy with rapamycin treatment is sufficient to lower NF-[Formula: see text]B signaling in the gut. Our research suggests that autophagic impairment in GD flies drives microbiome dysbiosis and chronic immune activation, with deleterious consequences on organismal health. We highlight pharmacological activation of autophagy, targeting tissues such as the gut, as a potential therapeutic strategy in GD.AbbreviationsAMP, antimicrobial peptide; DAMP, damage associated molecular pattern; GBA1, glucosylceramidase beta 1; LC3, microtubule-associated protein 1 light chain 3; MEGF10, multiple EGF like domains 10; mTOR, mammalian target of rapamycin; PGRP, peptidoglycan recognition protein receptor; TRIF, Toll/IL-1R domain-containing adaptor-inducing IFN-β.